2020
DOI: 10.1371/journal.pone.0233295
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of contrast sensitivity in eyes with epiphora due to lacrimal passage obstruction

Abstract: Epiphora causes deterioration in contrast sensitivity in some eye diseases. This study was conducted to investigate contrast sensitivity in eyes with epiphora caused by lacrimal passage obstruction. Methods This single-center, prospective case series enrolled 57 patients with unilateral lacrimal passage obstruction. The best-corrected visual acuity (BCVA), contrast sensitivity function, and lower tear meniscus of the affected and contralateral unaffected eyes were compared. The area under the log contrast sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…For example, dry eyes or eyes that underwent LASIK intervention show deterioration of contrast sensitivity, while their visual acuity remains unaffected [ 23 , 24 ]. In line with these findings, we previously reported a reduction in contrast sensitivity in eyes with epiphora caused by lacrimal passage obstruction, in which conventional visual acuity is maintained [ 1 ]. A contrast sensitivity test is also useful for evaluating the quality of vision before and after treatment in various anterior segment disease of the eyes, such as dry eye [ 25 , 26 ], ptosis and dermatochalasis [ 27 ], conjunctivochalasis [ 28 ], and cataract [ 29 ], as well as posterior segment eye diseases such as retinal detachment [ 30 ], epiretinal membrane [ 31 ], and posterior vitreous detachment [ 32 ], among others [ 33 ].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…For example, dry eyes or eyes that underwent LASIK intervention show deterioration of contrast sensitivity, while their visual acuity remains unaffected [ 23 , 24 ]. In line with these findings, we previously reported a reduction in contrast sensitivity in eyes with epiphora caused by lacrimal passage obstruction, in which conventional visual acuity is maintained [ 1 ]. A contrast sensitivity test is also useful for evaluating the quality of vision before and after treatment in various anterior segment disease of the eyes, such as dry eye [ 25 , 26 ], ptosis and dermatochalasis [ 27 ], conjunctivochalasis [ 28 ], and cataract [ 29 ], as well as posterior segment eye diseases such as retinal detachment [ 30 ], epiretinal membrane [ 31 ], and posterior vitreous detachment [ 32 ], among others [ 33 ].…”
Section: Discussionsupporting
confidence: 71%
“…Improvement in AULCSF was not correlated with changes in tear meniscus parameters in this study. Our previous study including unilateral lacrimal passage obstruction cases also revealed no correlation between AULCSF and tear meniscus parameters [ 1 ]. Similarly, Koh et al reported that tear meniscus parameters were not correlated to the quality of vision or optical quality in patients with epiphora owing to nasolacrimal passage obstruction [ 2 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Epiphora due to lacrimal passage obstruction can worsen visual function and vision-related quality of life. 8 , 9 , 10 Since patients with epiphora after RAI tend to be around age 50, which seems younger than primary acquired nasolacrimal duct obstruction, the negative effect of epiphora on social activity is a concern. 3 , 11 Dacryoendoscopic examination in patients with epiphora after radioiodine therapy may detect early-stage nasolacrimal obstruction/stenosis, which can be resolved by recanalization and insertion of the lacrimal tube, without the need for a more-invasive surgical approach such as dacryocystorhinostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Tear meniscus status is thought to affect visual function. Functional visual acuity, contrast sensitivity, and higher-order aberrations (HOAs) have been reported as indicators that re ect the ocular surface conditions impacted by tear meniscus dimensions [18][19][20][21]. In patients with lacrimal passage obstruction, normalizing the tear meniscus through surgical intervention is expected to result in good visual function.…”
Section: Introductionmentioning
confidence: 99%